(untitled) (Italian Journal of Public Health, 2012)
Background: oral health is an important aspect of well-being. In Italy immigrants can have different access to health care services, and can opt for the national Health Service (nHS) and/ or private non- profit health care organizations. The purpose of this study was to develop an instrument to evaluate oral health in the immigrant population of rome and to investigate the differences between two different types of ser- vices: the First observation unit at the department of oral and Maxillo Facial Sciences, at the “Sapienza” university of rome (a nHS affiliate), and a charitable organization, the caritas dental center (cdc). MeTHodS: a multiple-choice questionnaire was administered between the last trimester of 2006 and the first trimester of 2007. a chi square analysis was performed and the level of significance was set at p<0.05. reSulTS: The sample was composed of 250 people, of which 100 were patients of the cdc and 150 were patients of the nHS. The percentage of non-Italians was 80% (n=80) in the cdc sample, and only 16% (n=25) in the nHS sample. In the cdc, definitive resolving therapies, such as tooth extractions, prevailed (60% v’s 47% nHS; p=0.033). In addition, the frequency of consumption of sugary foods and drinks was significantly higher among cdc patients (31% reported to consume these over 9 times a day) compared to nHS patients (11% reporting this consumption). dIScuSSIon: The study shows a substantial under using of the national Health Service for oral health care needs by the immigrant population. The particular composition of the sample, with a high prevalence being of romanian nationality, might reflect specific conditions of this nationality. The results showed that immigrants were satisfied with the health care even though they encountered difficulties in terms of level of communication .